Global Perspectives on Media, Politics, Immigration, Advertising, and Social Networking - Kamalipour, Yahya R. (Cambridge Scholars Publisher, 2019)
This eclectic and multicultural volume contains 17 papers, authored or co-authored by 25 scholars and doctoral students representing 11 countries. They discuss a wide range of global issues, including immigration, marginalization, identity, mass media, politics, social networking, education, digital media, advertising, and globalization. This book will be an excellent supplement to senior and graduate-level courses in international communication, cultural studies, mass media, journalism, global studies, political communication, intercultural communication, and related subjects.